Complementary split ring resonator‐based microstrip antenna for compact wireless applications. Issue 4 (27th February 2013) - Laila, D.; Sujith, R.; Shameena, V.A.; Nijas, C.M.; Sarin, V.P.; Mohanan, P.
Abstract A compact circular patch antenna operating at 2.48 GHz using multiple ring complementary split ring resonator (multiple ring CSRR) in the ground plane is presented.The resonant frequency depends on the parameters of the CSRR. The antenna is fabricated on a substrate of dielectric constant (εr) 4.4 and the thickness (h) 1.6 mm. A size reduction of 83% is achieved compared to standard circular patch antenna working at the same frequency. © 2012 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:814–816, 2013; View this article online at wileyonlinelibrary.com. DOI: 10.1002/mop.27429